A Comparative Study of Safety and Efficacy of Clopidogrel and Prasugrel in Reducing Major Adverse Cardiovascular Events after Percutaneous Coronary Intervention - Chowdhury, Koustuv; Dolui, Sanat Kumar; Basu, Subrata; Sur, Arindam (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Elective PCI involves a lot of patient preparation particularly regarding themodulation of platelet and coagulation function in the periprocedural period. Clopidogrel, whenadded to aspirin, has demonstrated considerable success at reducing thrombotic complicationsof acute coronary syndrome (ACS) and/or percutaneous coronary intervention (PCI) comparedto aspirin alone. Whereas prasugrel is a novel antiplatelet agent that recently received Food andDrug Administration (FDA) approval for the treatment of patients with ACS undergoing PCI.Objective: Comparison of efficacy and safety of clopidogrel and prasugrel in reducing MACE(major adverse cardiovascular events) after PCI. Methods: The study was a parallel group,randomized, controlled single blinded, unicentric study. The study was conducted betweenJanuary 2021 and June 2022, in the Cardiac Catheterization Lab of Department of Cardiology,ICVS, R G Kar Medical College and Hospital, West Bengal, India. In this study, consecutive adultpatients, >20 years of age, of both sexes, undergoing elective PCI at the Cath Labs of Departmentof Cardiology, fulfilling the inclusion criteria within the specified period of time were evaluated.Results and Conclusion: Prasugrel is more effective than clopidogrel in preventing complicationsof PCI. It has significantly better favorable outcomes of PCI than clopidogrel. Prasugrel use resultsin more adverse events in PCI than clopidogrel, but the adverse events are minor in nature. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 328-334